Oxygen semi-permeation properties of La1−xSrxFeO3−δ perovskite membranes under high oxygen gradient. Issue 18 (28th September 2020) - Deronzier, Eva; Chartier, Thierry; Geffroy, Pierre-Marie
Abstract: Abstract : This work is focused on the evaluation of oxygen semi-permeation and electrochemical performances under high oxygen gradient of free cobalt perovskite membrane materials; La1− x Sr x FeO3−δ perovskite. For a better understanding of oxygen transport through La1− x Sr x FeO3−δ perovskite membranes, the oxygen diffusion, oxygen incorporation, and desorption coefficients were determined under high oxygen gradient in relation to the temperature for La1− x Sr x FeO3−δ (with x = 0.1, 0.3, 0.5, and 0.7) by a specific method based on oxygen semi-permeation. The best electrochemical performances were obtained for La0.3 Sr0.7 FeO3−δ (LSF37) and La0.5 Sr0.5 FeO3−δ (LSF55) perovskite membranes with oxygen fluxes of 1.7 × 10 −3 and 1.2 × 10 −3 mol/m 2 s at 900 °C, respectively. The oxygen incorporation and desorption coefficients of LSF55 were two times lower than those of LSF37 and similar to those of La0.5 Sr0.5 Fe0.7 Ga0.3 O3−δ . The values of these coefficients are discussed and compared with the data reported in the literature by isotopic exchange for the similar material compositions.